Ripoffs, Lemons, and Reputation Formation in Agency Relationships: A Laboratory Market Study - DEJONG, DOUGLAS V.; FORSYTHE, ROBERT; LUNDHOLM, RUSSELL J. (Journal of Finance, 1985)
ABSTRACT This paper examines the effect of the moral hazard problem in an agency relationship where the principal cannot observe the level of service provided by the agent. Using data from laboratory markets, we demonstrate that the presence of moral hazard leads to shirking by agents. However, this “lemons” phenomenon occurs only about one‐half of the time. While there is evidence of reputation effects in these markets, seemingly reputable agents are often able to use opportunities for false advertising to their advantage and “ripoff” principals.